Smoking Mechanics and Impact on Smoking Cessation: Two Cases of Smoking Lapse Status Post Lung Transplantation. (4th January 2022) - Galiatsatos, Panagis; Ekpo, Princess; Schreiber, Raiza; Barker, Lindsay; Shah, Pali
Background: Smoking behavior includes mechanisms taken on by persons to adjust for certain characteristic changes of cigarettes. However, as lung function declines due to lung-specific diseases, it is unclear how mechanical smoking behavior changes affect persons who smoke. We review two cases of patients who stopped smoking prior to and then subsequently resumed smoking after lung transplantation. Methods: A retrospective review of two patients who were recipients of lung transplantation and sustained from cigarette usage prior to transplantation. Results: Patient A was a 54-year-old woman who received a double lung transplant secondary to chronic obstructive pulmonary disease (COPD) in October 2017. She had stopped smoking cigarettes in July 2015 (FEV1 .56 L). Patient B was a 40-year-old man who received a double lung transplantation due to sarcoidosis in January 2015. He stopped smoking cigarettes in February 2012 (FEV1 1.15 L). Post-transplant, Patient A resumed smoking on March 2018 where her FEV1 was at 2.12 L (5 months post-transplantation), and Patient B resumed smoking in April 2017 where his FEV1 was 2.37 L (26 months post-transplantation). Conclusion: We report on two patients who resumed smoking after lung transplantation. While variations of smoking mechanics have been identified as a function of nicotine yield and type of cigarette, it lung mechanics may play a role in active smoking as well. Therefore, proper screening for tobacco usage post-lung transplantation should be considered a priority in order to preserve transplanted lungs.